2018
DOI: 10.1149/08512.0111ecst
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) Climbing over the Activity Volcano Correlation by Biomimicking Vitamin B12: A Co Phthalocyanine Pyridine Axial Ligand Coordinated Catalyst for the Reduction of Molecular Oxygen

Abstract: CoN4 macrocyclic complexes like Co phthalocyanines (CoPc) have been extensively studied as electrocatalysts for the ORR but they preferentially promote the 2-e reduction of O 2 to give peroxide. In contrast, vitamin B 12 , a naturally occurring CoN4 macrocyclic molecule alkaline media promotes the 4-electron reduction of O2 to H 2 O. Vitamin B12 possesses an imidazole axial back ligand and this seems to be the reason for its higher activity and selectivity for the 4-e reduction of O 2 . To test this hypothesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Cobalt macrocycles presented far higher activity than those containing copper. In 2018, Tasca et al [121], the same experiment was attempted for cobalt phthalocyanine. Two different aryl thiols, 4-aminothiophenol (ATP) and 1-(4-Mercaptophenyl)2,6-diphenyl-4-(4-pyridyl)pyridinium tetrafluoroborate (MDDP), were bound to Au (111) in the form of a self-assembled monolayer (SAM) and then CoPc was bound to them through their nitrogenous group (Fig.…”
Section: Cobalt Macrocyclesmentioning
confidence: 99%
See 2 more Smart Citations
“…Cobalt macrocycles presented far higher activity than those containing copper. In 2018, Tasca et al [121], the same experiment was attempted for cobalt phthalocyanine. Two different aryl thiols, 4-aminothiophenol (ATP) and 1-(4-Mercaptophenyl)2,6-diphenyl-4-(4-pyridyl)pyridinium tetrafluoroborate (MDDP), were bound to Au (111) in the form of a self-assembled monolayer (SAM) and then CoPc was bound to them through their nitrogenous group (Fig.…”
Section: Cobalt Macrocyclesmentioning
confidence: 99%
“…9 Diagrammatic representation of CoPc bound to Au (111) with 4 ATP (left) and MDDP (right). Adapted with permission from Riquelme et al [121]. Copyright (2018) The Electrochemical Society peroxide production was examined, it was observed that both catalysts show maximum production at 0.35 V which rapidly decreases in the case of CoPc-Py-CNT and takes an additional 0.250 V to reduce in the case of VitB12-CNT.…”
Section: Cobalt Macrocyclesmentioning
confidence: 99%
See 1 more Smart Citation
“…CoPc and CoPPc were mainly studied in the alkaline medium as electrocatalysts, where they were stable and not poisoned. [26][27][28][41][42][43][44][45][46] CoPc mainly performed the ORR through 2-electron and 4-electron mixed paths; 45,47 however, CoPPc 24 and pentacoordinated CoPc 43,46,48 showed higher activity and selectivity for the 4-electron ORR. So, in this work, the 4-electron reaction mechanism 49 was chosen to study the ORR activity of CoPPc and various CoPPc-L under alkaline conditions (pH = 14), and the Gibbs free energy change (DG) of each reaction step can be described as follows:…”
Section: Orr Mechanism Of Copc and Coppc-lmentioning
confidence: 99%
“…[43][44][45] It has been found that the introduction of suitable axial ligands on the central metal atom can effectively improve the catalytic performance of MN 4 complexes, because the axial ligands can change the electronic structure of the central metal atom, thus changing the adsorption strength of the catalyst to the reaction intermediate. 32,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] For instance, the strong interaction between cobalt phthalocyanine and nitrogen-rich carbon nitride leads to the formation of Co-N 5 catalytic sites, which can adjust the electronic structure of cobalt phthalocyanine and improve the electrocatalytic performance of cobalt phthalocyanine for CO 2 reduction. 70 Zhao et al reported that iron polyphthalocyanine axially coordinated by iodide ions exhibited good stability and catalytic performance.…”
Section: Introductionmentioning
confidence: 99%